Analisis Kemampuan Kolaborasi Peserta Didik Melalui Model Pembelajaran Kooperatif Tipe Group Investigation (GI) pada Pembelajaran PKn Kelas XI SMA Negeri 11 Samarinda - Dita Pramesti Irawan; Warman Warman; Jamil Jamil; Asnar Asnar; Marwiah Marwiah; Endang Herliah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research is based on the ability to collaborate which is an ability that students must have. Collaboration skills, what teachers must do to improve collaboration skills is to apply various learning models that adapt to students' needs. The Group Investigation type learning model is a learning model that focuses on students' collaboration abilities. The success of a learning process can be measured by the success of students in participating in the learning process.This research aims to explore the application of the group investigation model in an educational context and measure its impact in improving the collaboration abilities or skills of class XI students at SMA Negeri 11 Samarinda. The object of this research is all students in class XI C of SMA Negeri 11 Samarinda, totaling 36 students. This research is a qualitative descriptive type of research. The research method used in this research is a qualitative research method with a system of field observation, interviews and documentation. The data analysis technique used in this research is analysis.The concept of group investigation learning is learning that emphasizes students gaining knowledge through learning experiences. The group investigation type learning model has six stages, namely selecting topics, planning collaboration, implementing plans, analysis and synthesis, presenting work results, and evaluation.The collaboration ability of students in class And the results of interviews with students show that students have good collaboration or cooperation skills in completing the topic/material given.The advantage of the Group Investigation type Cooperative Learning learning model in class can improve students' ability to collaborate or work together and students can learn to solve problems that arise during the learning process.The weakness of the Group Investigation type Cooperative Learning learning model in class XI SMA Negeri 11 Samarinda namely, the material presented will be less because the learning time is short, the teacher will have difficulty giving individual grades, and the class atmosphere will be noisy due to discussions.